Stratified sampling for roots biomass quantification in shifting cultivation in Amazon Brazil - Rodrigues de Sousa, João Thiago; Lovatto, Mike; Soares dos Santos, Marllon Fernando; Germán Delgado, Santiago; Rodrigues de Lara, Idemauro Antonio (Brazilian Journal of Biometrics, 2024)
Several countries have been paying attention to carbon stocks and balances in the soil, a characteristic related to land management and use. Among the biomes that have great participation in the maintenance of these stocks, the Amazon biome stands out, which has great diversity by area. With the advances in markets aimed at buying carbon credits, estimates of the values of these stocks are highly susceptible to the intrinsic characteristics of the location. In order to solve these problems, several soil sampling techniques have been used to estimate these values. However, soil sampling techniques vary greatly in the amount of soil sampled, directly impacting the values of these estimates. In this sense, the present work aims to evaluate the point and interval estimates of carbon stocks in the soil in a peripheral region of the Brazilian Amazon, in the state of Maranhão. For this, three soil sampling techniques were compared, the large monolith (LM), the small monolith (SM) and the auger (RA). Considering a stratified sampling plan (STR), in which the different sampled depths are considered as strata, its efficiency was compared to a simple random sampling (SRS) and its amplitudes with the simulation through the Bootstrap technique. The samples were obtained by washing the samples and separating them into < 2mm and > 2mm for two biological groups (babassu roots and other roots). For interval estimates with the LM collection method, roots larger than 2 mm have a total of 2.56 to 4.62 t ha–1, and for smaller roots, 1.67 to 4.33 t ha–1. As for babassu roots, these values ranged from 0.38 to 1.44 t ha–1 and those smaller than 2 mm from 0.86 to 2.43. In contrast, the LM collection method can be replaced by SM and RA only for thick roots (> 2 mm). Regarding the STR sampling plan, the variance of the total was reduced in relation to the SRS. The bootstrap technique managed to reduce the amplitude of the intervals to the total, showing an improvement in accuracy. Therefore, estimates of carbon stocks can be made for the RA method for stored carbon, but the method for carbon that will return to the atmosphere the LM method is the most suitable.